CSFV Infection Up-Regulates the Unfolded Protein Response to Promote Its Replication - Wencheng He; Hailuan Xu; Hongchao Gou; Jin Yuan; Jiedan Liao; Yuming Chen; Shuangqi Fan; Baoming Xie; Shaofeng Deng; Yangyi Zhang; Jinding Chen; Mingqiu Zhao (Frontiers in Microbiology, 2017)
Classical swine fever (CSF) is an OIE-listed, highly contagious animal disease caused by classical swine fever virus (CSFV). The endoplasmic reticulum (ER) is an organelle in which the replication of many RNA viruses takes place. During viral infection, a series of events elicited in cells can destroy the ER homeostasis that cause ER stress and induce an unfolded protein response (UPR). In this study, we demonstrate that ER stress was induced during CSFV infection as several UPR-responsive elements such as XBP1(s), GRP78 and CHOP were up-regulated. Specifically, CSFV transiently activated IRE1 pathway at the initial stage of infection but rapidly switched off, likely due to the reduction in cytoplasm Ca2+ after viral incubation. Additionally, our data show that the ER stress induced by CSFV can promote CSFV production, which the IRE1 pathway play an important role in it. Evidence of ER stress in vivo was also confirmed by the marked elevation of GRP78 in CSFV-infected pig PBMC and tissues. Collectively, these data indicate that the ER stress was induced upon CSFV infection and that the activation of the IRE1 pathway benefits CSFV replication.